(untitled) (Archive of Conferences, 2021)
In this article, the development of knowledge, skills, competencies and scientific competence in the analysis of the specific methods of Abdurauf Fitrat’s novels in the process of teaching a competent approach to the subject of literature in general education in 11th grade students are achieved. Recommendations on specific methods of analysis of this work are also given.